Building a bridge: Knowledge sharing flows into entrepreneurial ecosystems - Roberta Andrade; Paulo Pinheiro; Luísa Cagica Carvalho; Raysa Geaquinto Rocha (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Entrepreneurial ecosystems remain under-theorised and conceptually fragmented, making it challenging to comprehend their disposition and performance in the business process. Accordingly, in this research, we explored how knowledge sharing flows through entrepreneurial ecosystems to make analyses and trials to assess new ventures' creation, continuity, and development opportunities. We carried out a systematic literature review on the Web of Science database. The analysis was carried out in two stages: (i) content analysis using NVivo software and (ii) statistical processing and clustering with the support of VOSviewer and Bibliometrix software. Moreover, we reviewed entrepreneurial literature and proposed conceptual model mapping relations through all main actors and knowledge flow in ecosystems. Our findings suggest the knowledge path in the near field sharing mechanisms resulting in a new conception of traditional structures and relations used to judge and decide how to assess opportunities for new ventures' opening, maintenance, and growth. This study contributes to entrepreneurial literature, demonstrating knowledge sharing flow through entrepreneurial ecosystems, considering an embracing, dynamic, and multilevel approach. Furthermore, it highlights political and social contributions to include new emergent perspectives: resource scarcity and structural and institutional gaps. This representation is the first knowledge management model applied to different economies and areas, respecting their singularities.
Keywords: 650; start-ups; bibliometric analysis; entrepreneurial ecosystems; knowledge sharing; systematic literature review